KORELASI ANTARA KEMAMPUAN MEMBACA DAN KEMAMPUAN MENULIS MAHASISWA SEMESTER EMPAT PROGRAM PENDIDIKAN BAHASA INGGRIS FKIP UNIVERSITAS RIAU - Handayani, Devi Handayani Devi; ', Eliwarti Eliwarti; ', Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This correlational research aimed to find out if there is any correlation between reading comprehension ability and writing ability of the fourth semester students of English Study Program FKIP Riau University. The population was the fourth semester students of English Study Program FKIP Riau University, they consisted of three classes: class A, class B and class C. In addition, class A was taken as the sample of this research. The writer used cluster sampling technique to decide the sample. The instrument of this research was two sets of tests; reading comprehension test and writing test. The students’ works were graded by the three raters and analyzed using pearson product moment formula. After the data were calculated, it was found that the value of rxy was 0.789. Then the writer compares value of rxy with r table with level of significance 5% (0.388) and 1% (0.496). Finally it was found that the value rxy of this study (0.789) was higher than the value of r in table product moment with level of significance 5% and 1%. It means that the alternative hypothesis was accepted, where it means that there is significant correlation between reading comprehension ability and writing ability of the fourth semester students of English Study Program FKIP Riau University was accepted. Then the writer also interpret the value of rxy with table interpretation of the value r by Best and Khan (2006) where the value of rxy (0.789) was in between 0.600 – 0.800 or in other words it was in substantial level. In conclusion, the correlation between reading comprehension ability and writing ability of the fourth semester students of English Study Program FKIP Riau University was significant in substantial level.Keywords: Reading Comprehension Ability, Writing Ability, Correlation, Pearson Product Moment